Differences in service and return in top 8 men and women ranking - Sánchez-Alcaraz Martinez, B. J.; Courel-Ibanez, J.; Sánchez-Pay, A.; Garcia Cambronero, S. (Coaching and Sport Science Review, 2018)
Our objective in this paper is to analyse the performance parameters in the serve and return of the top 8 men and women in their respective rankings in 2017. ATP and WTA service and return performance statistics were gathered from the top 8 men and women ranking in 2017. Findings have shown that the top 8 men and women win a higher percentage of points and games with the service than with the return, and they win more points with the first than with the second service. Men´s ranking registered higher values in service parameters, while women ranking showed a better performance in the return. Finally, male players with a higher position in the ranking have a higher percentage of break points saved and points won at service, something which was not so in the women's ranking. The results of this study help in understanding the differences in service and return parameters between male and female tennis.